Konsep Moderasi Beragama: Tantangan dan Peluang Terhadap Pendidikan Multikultural di Era Digitalisasi - Hasan, M. (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The development of the digital era and technology is increasingly rapid. In Indonesia, in this digital era, it is a challenge in the multicultural world, because technology is often misused, such as in using social media, there is a lot of access that has racist smacks, so this will give rise to various conflicts. For this reason, the concept of religious moderation really needs an education that talks about multiculturalism, which can teach people about the main values of multicultural education itself. With multicultural education in this digital era, it is hoped that technology can be utilized as well as possible. The research uses a literature study method with sources and review of references from journals that discuss this theme, namely the digital era and multicultural challenges in Indonesia. The aim of this research is so that readers, especially the nation's children, do not abuse technology in the digital era and are able to face multicultural challenges in Indonesia.